2017
DOI: 10.1111/inm.12365
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to group clinical supervision: A semistructured interview study of non‐participating mental health nursing staff members

Abstract: This present study is a report of an interview study exploring personal views on participating in group clinical supervision among mental health nursing staff members who do not participate in supervision. There is a paucity of empirical research on resistance to supervision, which has traditionally been theorized as a supervisee's maladaptive coping with anxiety in the supervision process. The aim of the present study was to examine resistance to group clinical supervision by interviewing nurses who did not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In particular, Hollander and Einwohner, and others (Johansson & Vinthagen, ; Baaz, Lilja, Schultz, & Vinthagen ), were germane in their assertion that resistance is defined not only by the resister's perception of her/his own behaviour, but also through the intersection of the perspectives of targets and others (including researchers) who recognise and react to this behaviour. While critics suggest that this typology may be incomplete as an analytical tool (Baaz, Lilja, Schultz, & Vinthagen ; Johansson & Vinthagen, ), others believe that the typology's strength lies in the assertion that analyses of resistance depend on perspective (Buus, Delgado, Traynor, & Gonge ).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Hollander and Einwohner, and others (Johansson & Vinthagen, ; Baaz, Lilja, Schultz, & Vinthagen ), were germane in their assertion that resistance is defined not only by the resister's perception of her/his own behaviour, but also through the intersection of the perspectives of targets and others (including researchers) who recognise and react to this behaviour. While critics suggest that this typology may be incomplete as an analytical tool (Baaz, Lilja, Schultz, & Vinthagen ; Johansson & Vinthagen, ), others believe that the typology's strength lies in the assertion that analyses of resistance depend on perspective (Buus, Delgado, Traynor, & Gonge ).…”
Section: Methodsmentioning
confidence: 99%
“…Stressful reactions to CS are also reported by mental health nurses due to work pressure that challenges in their ability to focus on the supervisory process (Buus et al, 2018). Moreover, the sharing of personal and intimate feelings and 'professional uncertainty' can feel very uncomfortable (Buus et al, 2018). Appropriate training and education for nurses prior to CS may help alleviate nurses' stressful experiences, and the importance of education for supervisees about the value of CS is evident in the findings of this synthesis.…”
Section: Discussionmentioning
confidence: 88%
“…Stressful reactions to CS are also reported by mental health nurses due to work pressure that challenges in their ability to focus on the supervisory process (Buus et al, 2018). Moreover, the sharing of personal and intimate feelings and 'professional uncertainty' can feel very uncomfortable (Buus et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the protected time afforded to supervisees, our data indicated that 'finding time' was still a challenge. Having protected time is a crucial component of supervision (Hall, 2018); nevertheless, staff who have engaged in clinical supervision (Cook et al, 2020;Dawson et al, 2012;Martin et al, 2016Martin et al, , 2019 and peer-group clinical supervision (Buus et al, 2018) consistently report time to engage as challenging. Dawson et al (2012) reported that although those who engage in supervision are afforded protected time, the commitment to attend supervision increases work-related pressure.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%